Security Architecture for Low Resource Devices in Smart City using Cloud - Muneer Ahmad Dar (JOIV : International Journal on Informatics Visualization, 2020)
The world is moving towards modernization with the help of smart devices used in smart cities to make the whole lot intelligent and smart. These smart devices are extensively used in smart city and are capable of doing everything which one can do with the normal desktop computer. These smart devices like Smartphone have computational limitations are not able to store a large data to be used and collected in a smart city. In this paper, we propose a novel security architecture which first uses the Elliptic Curve Diffie Helman Key Exchange Algorithms to exchange the keys between the two low power devices (Smartphone). The keys are used to encrypt the large data (images and videos etc). The data is encrypted using the private keys of a device and then send to the cloud for safe storage. The data can be only accessed by the communicating device with the same key. The proposed security architecture enables these smart devices to store the huge data collected from the smart city to store on the cloud. If another device requests the same set of data, the keys can be shared secretly and the communicating device can be allowed to download the data directly from the cloud. This architecture relieves the Smartphone from the storage limitation and also enables it to communicate with faster speed and securely.